If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 55 = 6(7m + -2) + 5(1 + 4m) Reorder the terms: 55 = 6(-2 + 7m) + 5(1 + 4m) 55 = (-2 * 6 + 7m * 6) + 5(1 + 4m) 55 = (-12 + 42m) + 5(1 + 4m) 55 = -12 + 42m + (1 * 5 + 4m * 5) 55 = -12 + 42m + (5 + 20m) Reorder the terms: 55 = -12 + 5 + 42m + 20m Combine like terms: -12 + 5 = -7 55 = -7 + 42m + 20m Combine like terms: 42m + 20m = 62m 55 = -7 + 62m Solving 55 = -7 + 62m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-62m' to each side of the equation. 55 + -62m = -7 + 62m + -62m Combine like terms: 62m + -62m = 0 55 + -62m = -7 + 0 55 + -62m = -7 Add '-55' to each side of the equation. 55 + -55 + -62m = -7 + -55 Combine like terms: 55 + -55 = 0 0 + -62m = -7 + -55 -62m = -7 + -55 Combine like terms: -7 + -55 = -62 -62m = -62 Divide each side by '-62'. m = 1 Simplifying m = 1
| 3x-x-8=-(x-10)+2x | | 5n-5-6+12n=-18 | | 4(1+8b)-8b=-140 | | k-10=-7/2 | | -3p+36=2(-8p+5) | | 2x+28=10x+40-4x | | n/2=n+3/8 | | -3.4162x=14.34804 | | (u^4)^2•v^-2/2vu^3 | | -(5a+6)-5(a-9)= | | 6c+3=44 | | 7x-5=-5x-29 | | 42y-77= | | 8/4=4/x | | -23+5r=7+35r | | 12x=3x-32 | | .01x+.10x+.25(53-2x)=5.84 | | x^2-6x+4x-14=9x-42 | | 5(c-8)-3(2c+n)=-84 | | -20+8n=-4(5-2n) | | 2g-13=4 | | 7x-5=5x-29 | | log(x)+log(x+1)=-1 | | 3n-5=2m+6 | | -9n-9=-23+5n | | 9x=0.012 | | 6x+5=-8+4x+19 | | 2/15=h/55 | | 21+(3-f)7=11 | | 2(s+3)-5s=30 | | y^-3•x^3y^-4/(y^3)^-2 | | 4f=.20*4 |